Crowding out informal care?: Evidence from a field experiment in Germany - Arntz, Melanie; Thomsen, Stephan L. (Oxford bulletin of economics and statistics, 2011)
This article evaluates the effects of a consumer-directed home care programme (Personal Budgets) compared with the standard home care programmes of the German long-term care insurance (LTCI). The evaluation makes use of a random assignment into a treatment group receiving personal budgets and a control group receiving either in-kind benefits (agency care) or cash payments. Compared with agency care, personal budgets extend the support by independent providers, but leave health outcomes unchanged. Compared with cash payments, personal budgets tend to improve health outcomes, but double LTCI spending due to a strong crowding out of informal care by formal care.
First published: 14 November 2010
Gesehen am 17.04.2019